PENGARUH KOMPOTENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, DAN PEMAHAMAN AKUNTANSI BERBASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA LEMBAGA PERKREDITAN DESA SE- KECAMATAN GIANYAR - Ni Kadek Gino Melinda; Putu Cita Ayu (UNHI Press, 2021)
The Village Credit Institution (LPD) is an economic institution in the village that is useful as a place to collect funds, provide credit, as well as a source of financing in development in the village area in Bali. The purpose of this research is to determine the effect of human resource potential, internal control systems, and understanding of acrual-based accounting on the quality of financial statements. The population used in this study were all LPD employees in Gianyar District, totaling 223 people with 40 LPDs located in Gianyar District with 80 employees selected as the research sample. Determination of the sample using Non Probability sampling with purposive sampling formula used as the sampling method in this study. Data analysis techniques include descriptive analysis, validity test, reliability test, classical assumption test, multiple regression analysis, F test, determination coefficient (R2), and t test. The results of this research showed that:(1) Human Resource Compotency hasta positive effect on the Quality of Financial Statements..(2) The Internal Control System has a positive effect on the Quality of Financial Statements.(3)Accrual Based Accountting Understanding has a positive effect on the Quality of Financialy Statements.